Recent Advances in Nanoporous Anodic Alumina: Principles, Engineering, and Applications - Jakub T. Domagalski; Elisabet Xifre-Perez; Lluis F. Marsal (Nanomaterials, 2021)
The development of aluminum anodization technology features many stages. With the story stretching for almost a century, rather straightforward—from current perspective—technology, raised into an iconic nanofabrication technique. The intrinsic properties of alumina porous structures constitute the vast utility in distinct fields. Nanoporous anodic alumina can be a starting point for: Templates, photonic structures, membranes, drug delivery platforms or nanoparticles, and more. Current state of the art would not be possible without decades of consecutive findings, during which, step by step, the technique was more understood. This review aims at providing an update regarding recent discoveries—improvements in the fabrication technology, a deeper understanding of the process, and a practical application of the material—providing a narrative supported with a proper background.